Health risk assessment of ciprofloxacin, tetracycline, and oxytetracycline residues in raw, frozen, and boiled broiler chicken available in a local area of Bangladesh - Haque, Shaila; Jamil, Md. Yusuf; Khan, Md. Shahinul Haque; Reza, Md. Sajib Al; Esrafil, Md.; Abedin, Md. Zainul; Zubair, Md. Abu; Sikder, Md. Asaduzzaman; Bari, Luthfunnesa (Frontiers in Antibiotics, 2024)
The misuse of antibiotics in poultry farming is a global issue. Objective: The health risk assessment of consumers was the focus of this study from the determination of ciprofloxacin, tetracycline, and oxytetracycline in broiler chicken at raw, frozen, and boiled stages by SPE-HPLC-UV. Materials and methods: The chromatographic separation was achieved using 0.3% metaphosphoric acid and acetonitrile (1:10; v/v) for ciprofloxacin (CIP) at 280 nm; oxalic acid (0.01M) and acetonitrile (1:1; v/v) for tetracycline (TC) and oxytetracycline (OTC) at 355 nm with different retention time. The method had an acceptable precision with good linearity, specificity, limit of detection, limit of quantification, accuracy, and stability. Results: Among 252 total raw samples, about 68.25%, 25.4%, and 7.54% contained CIP, TC and OTC respectively. Out of the positive raw samples, CIP exceeded maximum residual limit (MRL) in muscle 10.71%, liver 12.66% and skin samples 15.38% whereas TC and OTC were below the MRL. The residual concentration of those antibiotics was almost unchanged in frozen samples. After boiling chicken samples, TC and OTC residues were reduced significantly than CIP. Although the concentration of CIP in boiled samples were above the MRL set by EU but didn't exceed the hazard quotient index 1. Conclusion:Based on these results, the exposure levels to antibiotics in broiler chicken meats may be considered to have low risk for human health.